Strain rate effects on reinforcing steels in tension - Cadoni Ezio; Forni Daniele (EPJ Web of Conferences, 2015)
It is unquestionable the fact that a structural system should be able to fulfil the function for which it was created, without being damaged to an extent disproportionate to the cause of damage. In addition, it is an undeniable fact that in reinforced concrete structures under severe dynamic loadings, both concrete and reinforcing bars are subjected to high strain-rates. Although the behavior of the reinforcing steel under high strain rates is of capital importance in the structural assessment under the abovementioned conditions, only the behaviour of concrete has been widely studied. Due to this lack of data on the reinforcing steel under high strain rates, an experimental program on rebar reinforcing steels under high strain rates in tension is running at the DynaMat Laboratory. In this paper a comparison of the behaviour in a wide range of strain-rates of several types of reinforcing steel in tension is presented. Three reinforcing steels, commonly proposed by the European Standards, are compared: B500A, B500B and B500C. Lastly, an evaluation of the most common constitutive laws is performed.